Effectiveness Of Post-Disaster Soscio-Economic Assistance Programs In Pandeglang Regency, Banten Province - Ani Suryani; Lijan Poltak Sinambela (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze and determine the effectiveness of the post-disaster recovery socioeconomic assistance program in Pandeglang Regency, Banten Province, and to identify the factors that support and hinder the effectiveness of the socioeconomic assistance program in post-disaster recovery efforts in Pandeglang Regency, Banten Province. The focus of the study is on the implementation of the 2020 economic assistance program and the 2021 social assistance program, as well as the identification of supporting and inhibiting factors. The approach used is a qualitative approach with a case study method. Data was collected through in-depth interviews, documentation studies, and field observations of policy implementers, beneficiary groups, and relevant stakeholders. Data analysis was conducted descriptively using Edy Sutrisno's (2010) program effectiveness theory with effectiveness measurement indicators in the form of program understanding, target accuracy, timeliness, goal achievement, and tangible changes.The results of the study show that the implementation of post-disaster socioeconomic assistance programs has not been effective. Of the five indicators, two indicate ineffective results, namely goal achievement, and tangible changes, while the indicators of program understanding, target accuracy, timeliness indicate effective results. The factors supporting the effectiveness of the socioeconomic assistance program are coordination and cooperation between BNPB and the implementation team, program socialization, supervision/monitoring by BNPB, and the capacity of human resources/the implementation team. Meanwhile, the factors hindering the effectiveness of the post-disaster socioeconomic assistance program in Pandeglang Regency include suboptimal product marketing support, the absence of technical regulations that form the basis for local government support, the characteristics of the program beneficiaries, and the Covid-19 pandemic.